HUBUNGAN LAMA MEROKOK DENGAN KEJADIAN HIPERTENSI DI PUSKESMAS KENYARAN KECAMATAN PANTAN CUACA KABUPATEN GAYO LUES TAHUN 2019 - Dewi Ramadani; Hamidah (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2019)
Hypertension is the silent disease because people do not know that they are exposed to hypertension due to prolonged smoking. The purpose of this study is to determine the relationship between smoking duration and the incidence of hypertension in Kenyaran Health Center, Pantan Weather, Gayo Lues Regency in 2019. This type of research is quantitative research, The research design used is descriptive correlation with cross sectional approach. The population in this study was hypertension sufferers. The total sampling technique was 30 people. Chi-square test results obtained a significant value P value (0.001) <(0.05) there is a significant relationship between the duration of smoking with the incidence of hypertension in Kenyaran Public Health Center in Pantan Weather Gayo Lues District in 2019. The conclusion of this study is that cigarettes contain nicotine which can increase the hormone epinephrine which can constrict arterial blood vessels. It is recommended to health workers to provide counseling about the dangers of smoking for people with hypertension.